Successful termination of sustained transmission of resident MRSA following extensive NICU refurbishment: an intervention study. Issue 3 (November 2018) - Semple, A.; O'Currain, E.; O'Donovan, D.; Hanahoe, B.; Keady, D.; Ní Riain, U.; Moylett, E.
Summary: Background: Neonatal sepsis is a leading cause of morbidity and mortality in neonatal units worldwide. Meticillin-resistant Staphylococcus aureus (MRSA) has become a leading causative pathogen. Many neonatal units experience endemic colonization and infection of their infants, which is often very challenging to successfully eradicate. Aim: To assess the impact of neonatal unit refurbishment and redesign on endemic MRSA colonization and infection. Methods: A retrospective review was carried out over an eight-year period in a 14-cot, level 2–3 neonatal unit in University Hospital Galway, a large university teaching hospital in the West of Ireland. Surveillance, colonization, and infection data for a four-year period pre and four-year period post neonatal unit refurbishment are described. Clinical and microbiological data were collected on all MRSA-colonized and -infected infants between 2008 and 2015. Molecular typing data are available for MRSA isolates. An interrupted time-series design was used, with unit refurbishment as the intervention. Findings: Our neonatal unit had a pattern of sustained transmission of endemic resident MRSA strains which we could not eradicate despite repeated standard infection control interventions. Complete unit refurbishment led to successful termination of sustained transmission of these strains. Colonization decreased and no infants were actively infected post refurbishment of the unit. Conclusion: We report successful termination of sustained transmission of endemic strains of MRSA from our neonatal unit following complete unit redesign and refurbishment.